2017
DOI: 10.17352/ojtr.000003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delay Separation and Short Term Storage of Serum on Thyroid Stimulating Hormone (TSH)

Abstract: Introduction: Thyroid stimulating hormone (TSH) regulates the level of thyroid hormones synthesized in the thyroid gland. Its measurement greatly facilitates the clinical diagnosis as well as management of pituitary-thyroid diseases. The level of analytes in biological sample is affected by pre-analytical, analytical and post-analytical factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…We found no difference across centrifugation timings in serum TSH concentration upto 24 hours after blood collection. Similar findings were also documented by Basanta et al 9 in a study conducted in Nepal in 2017. This study revealed that, TSH measurement might be applicable in large epidemiological studies, which require very long transportation time to reach samples to the…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found no difference across centrifugation timings in serum TSH concentration upto 24 hours after blood collection. Similar findings were also documented by Basanta et al 9 in a study conducted in Nepal in 2017. This study revealed that, TSH measurement might be applicable in large epidemiological studies, which require very long transportation time to reach samples to the…”
Section: Discussionsupporting
confidence: 90%
“…Sampling technique used was non-probability convenience sampling. Sample size was calculated using EPI info Statistical calculator by using frequency of pre analytical variables affecting thyroid assay published in article Basanta et al in 2017 9 . Individuals with history of chronic illness, obstetric event (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a more recent study found that TSH assays performed on sera from fifteen patients that were immediately assayed, then assayed after standing at room temperature for 24h, and then assayed after storage at 4 o C for one week, all gave values that were statistically insignificantly different 8 . An early comprehensive study of thyroid function test stabilities found significant differences in all thyroid function tests depending on ambient temperature 9 .…”
Section: Introductionmentioning
confidence: 80%